Joint Probabilistic Analysis of Risk for Aquatic Species and Exceedence Frequency for the Agricultural Use of Chlorpyrifos in the Pampean Region, Argentina - Alvarez, Melina Andrea (2019)
The Pampa Húmeda region in Argentina is characterized by soybean, wheat, andmaize production, with intensive application of agrochemicals such as herbicides and insecticides. We used a joint probabilistic approach to analyze the probabilities for environmental chlorpyrifos concentrations measured in the Pampa Húmeda to exceed acute or chronic Hazard Concentration-5 (HC5) values estimated from Species Sensitivity Distributions (SSD) for aquatic species. Chlorpyrifos concentrations in water ranged from 0.0005 to 10.8 µg/L with a median of 0.013 µg/L. The HC5 limits were 0.0637 µg/L for acute and 0.0007 µg/L for chronic effects. The probabilities for chlorpyrifos environmental concentrations to exceed the HC5 values ranged from 35% (acute effects) to 96% (chronic effects). Water Quality Criteria (WQC) for the protection of aquatic life were also frequently exceeded (48%-87%) for both acute and chronic effects. Together with published threshold limit values from mesocosm studies, these data suggest that macroinvertebrate communities can be severely affected by the reported environmental concentrations of chlorpyrifos. Indeed, changesin the macroinvertebrate assemblage in the Pampa Húmeda have been correlated with chlorpyrifos levels in sediments. Nevertheless, the actual impact needs to be ascertained by assessing the recovery rate of macroinvertebrate populations in this region. Considering the HC5 for chronic effects and the threshold limits for macroinvertebrate community level effects, we propose 0.7 ng/L as a new WQC to effectively protect aquatic life from long-term exposure to chlorpyrifos.